KONTRIBUSI BAWASLU KOTA BENGKULU DALAM MENYELENGGARAKAN PEMILU 2024 - Nedy Ramadhan Syaputra; Rosidin Rosidin; Rekho Adriadi; Titi Darmi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to analyze the role of the Election Supervisory Agency (Bawaslu) of Bengkulu City in implementing the supervision of the 2024 Simultaneous Election and identify the obstacles faced. The research method used is a qualitative approach with a case study type. Data collection techniques were carried out through in-depth interviews, observation, and documentation, with triangulation techniques to test the validity of the data. The results of the study indicate that the Bengkulu City Bawaslu carried out supervision actively, participatory, and adaptively through preventive, repressive, and educational approaches. Supervision was carried out directly in the field and digitally using the SIWASLU system. However, there were obstacles in terms of the number of supervisors, budget limitations, political pressure, and low public participation. This study suggests strengthening human resource capacity, utilizing technology, and increasing public political literacy to increase the effectiveness of election supervision. Keywords: Bawaslu, election supervision, democracy, Bengkulu City, 2024 Election